China and the globalization of biomedicine - Luesink, David, 1974-; Schneider, William H. (William Howard), 1945-; Zhang, Daqing, 1959- (Rochester studies in medical history., 2019)
"Argues that developments in biomedicine in China should be at the center of our understanding of biomedicine, not at the periphery"--